Ice Shakes Enterprise / Muhd. Safwan Sulaiman ... [et al.] - Sulaiman, Muhd. Safwan; Hanafiah, Mohd. Haafiq; Abdul Rachim, Abdul Mutalib; Raden Amin Othman, Raden Adi Islam; Raffy, Rafidah; Mohamad Yusuf, Sofinatinsyah (2014)
Beverage industry is one of the biggest contributors in Malaysia's economy and it has been proved the industry consistent growth in the Food and Beverage Global Report 2013. Malaysia has high potential in business, plus our government wants the local to get involved in this field. We have form a partnership named Ice Shakes. Ice Shakes is the new firm that involves in the beverages in Malaysia to provide variety flavored ice drinks to satisfy customers. Our name represented our main product, which are flavored ice drinks. It is represented ice and customers clearly know our business product by our firm's name. Since our business nature is partnership business, the profit sharing will be based on the capital contribution by each partner. Ice Shakes will provide variety flavored of ice drinks including flavored ice blended, fresh fruits ice blended, and variety mixed and match ice drinks. Every drink can be added additional on such as chocolate chips, Oreo, chocolate rice and many more. We have agreed to set our business location at Centre Point Kota Kinabalu in the ground floor because it has great opportunity in that location. Centre Point is one of the popular shopping mall and frequently visited among local and tourist. We have scheduled our business will be started on 1st January 2014. Our entire organization plan, marketing plan, operation plan and finance plan has been prepared before the commenced date.